Fitness, fatness, and academic performance in seventh-grade elementary school students - Sardinha, Luís B (BioMed Central, 2014)
BACKGROUND: In addition to the benefits on physical and mental health, cardiorespiratory fitness has shown to have positive effects on cognition. This study aimed to investigate the relationship between cardiorespiratory fitness and body weight status on academic performance among seventh-grade students. METHODS: Participants included 1531 grade 7 students (787 male, 744 female), ranging in age from 12 to 14 years (M(age) = 12.3 ± 0.60), from 3 different cohorts. Academic performance was measured using the marks students had, at the end of their academic year, in mathematics, language (Portuguese), foreign language (English), and sciences. To assess cardiorespiratory fitness the Progressive Aerobic Cardiovascular Endurance Run, from Fitnessgram, was used as the test battery. The relationship between academic achievement and the independent and combined association of cardiorespiratory fitness/weight status was analysed, using multinomial logistic regression. RESULTS: Cardiorespiratory fitness and weight status were independently related with academic achievement. Fit students, compared with unfit students had significantly higher odds for having high academic achievement (OR = 2.29, 95% CI: 1.48-3.55, p < 0.001). Likewise, having a normal weight status was also related with high academic achievement (OR = 3.65, 95% CI: 1.82-7.34, p < 0.001). CONCLUSIONS: Cardiorespiratory fitness and weight status were independently and combined related to academic achievement in seventh-grade students independent of the different cohorts, providing further support that aerobically fit and normal weight students are more likely to have better performance at school regardless of the year that they were born.